2021
DOI: 10.1186/s40104-021-00645-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and combined effects of N-[2-(nitrooxy)ethyl]-3-pyridinecarboxamide and fumaric acid on methane production, rumen fermentation, and lactation performance in dairy goats

Abstract: Background In recent years, nitrooxy compounds have been identified as promising inhibitors of methanogenesis in ruminants. However, when animals receive a nitrooxy compound, a high portion of the spared hydrogen is eructated as gas, which partly offsets the energy savings of CH4 mitigation. The objective of the present study was to evaluate the long-term and combined effects of supplementation with N-[2-(nitrooxy)ethyl]-3-pyridinecarboxamide (NPD), a methanogenesis inhibitor, and fumaric acid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, its use is facing decreased levels of social acceptance due to the potential impacts on public health [ 6 , 7 ] and has been banned in the European Union and limited in China. Recently, many works have been conducted to search for potential alternatives for monensin [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, its use is facing decreased levels of social acceptance due to the potential impacts on public health [ 6 , 7 ] and has been banned in the European Union and limited in China. Recently, many works have been conducted to search for potential alternatives for monensin [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021). Dairy products evaluated in different studies included kefir (Cais-Sokolińska et al ., 2015), milk (all other papers) and, additionally, cheese (Ianni et al ., 2019; Bonanno et al ., 2019a, 2019b; Menci et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…There were studies whose interventions were based on food components like durum wheat bran (Bonanno et al ., 2019b), grape pomace or marc (Ianni et al ., 2019; Scuderi et al ., 2019) and mushroom myceliated grains (Bonanno et al ., 2019a). Intervention with isolated bioactive compounds included plant bioactive lipid compounds plus biotin and monensin (Hausmann et al ., 2018), hesperidin or naringin or α-tocopheryl acetate (Simitzis et al ., 2019), tannin extract (Menci et al ., 2021), and finally N-[2-(nitrooxy) ethyl]-3-pyridinecarboxamide combined with fumaric acid (Li et al ., 2021). The main beneficial effects of the dairy interventions are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Supernatants were separated from samples for testing SCFA concentrations, and the pellets were used for metagenomic shotgun sequencing. The SCFA concentrations in the fermentation broth were analyzed according to the procedures of Li et al 14 In short, 1 mL of 25% metabolic acid was added to 5 mL of fermentation broth sample, and the mixture was centrifuged for 15 min at 13000g at 4 °C. Then, the supernatant was collected and mixed with 200 μL of crotonic acid (1%, w/v) and filtered through a 0.45 μm filter.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%